2018
DOI: 10.3892/ol.2018.7932
|View full text |Cite
|
Sign up to set email alerts
|

Silencing LDHA inhibits proliferation, induces apoptosis and increases chemosensitivity to temozolomide in glioma cells

Abstract: Abstract. Glioblastoma multiforme (GBM) is a prevalent and aggressive disease, and the development of a novel therapy to better treat advanced GBM is urgently required. Lactate dehydrogenase A (LDHA), which functions as a key enzyme in transforming pyruvate into lactate, has attracted more attention in recent years due to its critical role in various types of advanced cancer. Previous data derived from the Oncomine database have shown that the expression of LDHA is higher in GBM tissues than that in correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…In different brain tumors, high lactate dehydrogenase (LDH) activity and an abnormal LDH isoform expression pattern was observed by Subhash et al [131], who analyzed 100 biopsy samples. Additionally, Di et al [132], investigating clinical samples, confirmed a positive correlation between LDHA expression and glioma grade. Moreover, silencing LDHA expression with siRNA in human GBM cell lines U87MG and U251MG resulted in growth inhibition and enhanced sensitivity to TMZ [132].…”
Section: Reversing Lactate Effectsmentioning
confidence: 87%
See 1 more Smart Citation
“…In different brain tumors, high lactate dehydrogenase (LDH) activity and an abnormal LDH isoform expression pattern was observed by Subhash et al [131], who analyzed 100 biopsy samples. Additionally, Di et al [132], investigating clinical samples, confirmed a positive correlation between LDHA expression and glioma grade. Moreover, silencing LDHA expression with siRNA in human GBM cell lines U87MG and U251MG resulted in growth inhibition and enhanced sensitivity to TMZ [132].…”
Section: Reversing Lactate Effectsmentioning
confidence: 87%
“…Additionally, Di et al [132], investigating clinical samples, confirmed a positive correlation between LDHA expression and glioma grade. Moreover, silencing LDHA expression with siRNA in human GBM cell lines U87MG and U251MG resulted in growth inhibition and enhanced sensitivity to TMZ [132]. Consistent results, confirming that LDHA upregulation results from a lack of cyclin G2-mediated inhibition of LDHA activity, were obtained by Li et al [133], who also employed the U87 and U251 plus mouse GL261 glioma cell lines.…”
Section: Reversing Lactate Effectsmentioning
confidence: 87%
“…Additionally, an acidified microenvironment is likely to induce cell matrix degradation, microvessel formation and the Warburg effect (29). Moreover, silencing LDHA inhibited proliferation, induced apoptosis and increased the chemosensitivity of glioma cells to temozolomide (30). This indicates that PTX may effectively inhibit cancer cell growth and achieve its therapeutic effect by mediating the expression of glycolysis-related apoenzymes in GSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HIF-1α is aberrantly expressed and inversely associated with prognosis in GBM patients [46]. Moreover, either suppressing HK2 activity by its inhibitor 3-bromopyruvate or downregulating LDHA by siRNA inhibits the malignant phenotype of glioma cells, suggesting that HIF-1α-responsive genes related to glycolysis could be potential targets for glioma treatment [47,48]. It has been well established that RLIP76 has a close association with several HIF-1αrelated genes, such as VEGFA and AKT, which leads to malignant development of gliomas [45,49].…”
Section: Discussionmentioning
confidence: 99%